Structural evolution of the Cape Smith Belt from initial thrusting to basement-involved folding - Lucas, S.; St-Onge, M. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary Structures in the Cape Smith Belt record the transition during collisional deformation from (1) initial thin-skinned thrust belt growth, to (2) internal thickening of the thrust belt involving basement thrusting, and finally to (3) basement-involved, crustal-scalefolding. Overprinting deformation-metamorphism relationships allow recognition of four principal stages in the history of the thrustbelt. First, south-verging, regular (piggy-back)-sequence thrusts developed above aregional basal décollement which was localized at the basement-cover contact Second, thermal equilibration of the thrust belt(20 to 30 km thick) resulted in metamorphism and the development of a ductile shear zone at its base. Third, major out-of-sequence thrust faults internally deformed the thrust belt from pre- to post-thermal peak conditions. Finally, thrust belt deformation (D,) was followed by an episode of basement- (footwall-) involved folding (D?) which continued to accommodate the north-south shortening.